Необхідність удосконалення методик формування знань щодо психології безпеки професійної діяльності у фаховій підготовці майбутніх інженерів, психологів та викладачів вищої школи - Ігнатюк, Ольга Анатоліївна; Демідова, Юлія Євгенівна (Класичний приватний університет, 2015)
У статті обґрунтовано важливість формування знань з психології безпеки професійної діяльності у фаховій підготовці студентів інженерного та психолого-педагогічного профілю. Запропоновано практичні кроки з удосконалення методик формування відповідних знань безпеки діяльності, розвитку стійких навичок безпечних прийомів праці, формування загальної культури безпеки на всіх рівнях виробничого алгоритму.

The article focuses on the importance of the process of training of students of engineering and psycho-pedagogic knowledge formation in psychology security profession. The practical steps that will determine the improvement of methods of forming appropriate knowledge of security activities, the development of sustainable skills of safe work methods, the formation of a common safety culture at all levels of production of the algorithm are characterized in the article. It is important to show the connection of this area with the general direction of solving production problems: technical, social and economic. The authors note that such a problem becomes complex and must be realized not only in the study of the humanities and the social and psychological and pedagogical disciplines, but also in the process of training in the study of special subjects. It is shown that the main components of the system security knowledge generation activities are: professional and comprehensive safety training activities; possession of principles, methods and means of ensuring the safety and ability to find optimal solutions-based organizational, administrative and technical nature for each specific case, understanding the essence of the proposed solutions and their possible consequences. The authors note that formation of such a system of knowledge will determine the relation between the individual disciplines and subspecialties safety activities.
The need for Improved Methods of Forming Knowledge in Psychology Security Professional Work in the Training of Future Engineers, Psychologists and Teachers of High School
Keywords: підготовка професійна; підготовка фахівців; підготовка кадрів; зміст освіти; процес навчально-виховний; охорона праці; орієнтація професійна; security activities; culture; skills; professional; engineer; teacher